2013
DOI: 10.1017/s1368980013002206
|View full text |Cite
|
Sign up to set email alerts
|

The use of predefined diet quality scores in the context of CVD risk during urbanization in the South African Prospective Urban and Rural Epidemiological (PURE) study

Abstract: Objective: Urbanization is generally associated with increased CVD risk and accompanying dietary changes. Little is known regarding the association between increased CVD risk and dietary changes using approaches such as diet quality. The relevance of predefined diet quality scores (DQS) in non-Western developing countries has not yet been established. Design: The association between dietary intakes and CVD risk factors was investigated using two DQS, adapted to the black South African diet. Dietary intake data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…The results of the ideal CVH gradient from the rural Ghana through urban Ghana to Europe are consistent with the studies on rural through urban and high-income countries on cardiovascular disease risk factors [ 22 – 26 ]. This is very much a tribute to the impact of environmental factors on the constituent CVH metrics.…”
Section: Discussionsupporting
confidence: 88%
“…The results of the ideal CVH gradient from the rural Ghana through urban Ghana to Europe are consistent with the studies on rural through urban and high-income countries on cardiovascular disease risk factors [ 22 – 26 ]. This is very much a tribute to the impact of environmental factors on the constituent CVH metrics.…”
Section: Discussionsupporting
confidence: 88%
“…The QFFQ data was computerized using the FoodFinder3 Âź program (Medical Research Council, Tygerberg, South Africa) and sent to the Medical Research Council of South Africa for computerization, verification and nutrient analysis based on the most recent South African Food Composition Tables. Two predefined diet quality scores, the Healthy Diet Indicator and Adapted Thiele dietary quality score, were adapted and calculated, as previously described [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, intakes of fruit and vegetables are very low in South Africans. The PURE study reported median intake values of less than 150 g for rural and urban men and women [ 35 ] in comparison with the recommendation of at least 400 g per day. In addition, the data on the PURE study also indicates a higher intake of micronutrients in the urban than rural South Africans with large percentages of participants not meeting the DRIs [ 24 ].…”
Section: Interpreting the Findingsmentioning
confidence: 99%